Healthcare providers' intention to discriminate against people with HIV - Idris, Almutaz M.; Crutzen, Rik; van den Borne, Hubertus W.; Stutterheim, Sarah E. (Frontiers in Public Health, 2025)
BackgroundHealthcare providers' discrimination practices against people with HIV is a real challenge for control and prevention efforts. The study aims to explore the association between healthcare providers' intention to discriminate against people with HIV and HIV stigma-related constructs, their sociodemographic, and occupation characteristics in Sudan.MethodsA cross-sectional survey of healthcare providers was carried out in governmental hospitals in Kassala State, Sudan. Respondents completed measures assessing their intentions to discriminate against people with HIV, HIV-related stigma constructs, sociodemographic, and occupational characteristics. Bivariate and multiple linear regression analysis were used to assess the associations between discriminatory intentions against people with HIV and the studied variables.ResultsA total of 387 participants (223 physicians and 164 nurses) completed the survey. Participants had relatively high intentions to discriminate against people with HIV (M = 5.19, SD = 1.34—on a scale from 1 to 7), prejudiced attitudes (M = 4.70, SD = 1.29), internalized shame about HIV (M = 5.19, SD = 1.34), fear of HIV (M = 4.65, SD = 1.39), and the belief that patients with HIV do not deserve good care (M = 4.90, SD = 1.35). Healthcare providers' intention to discriminate against people with HIV was associated with prejudiced attitudes, internalized shame about HIV, fear of HIV, and the belief that people with HIV do not deserve good care. Female health care providers, nurses, and those with postgraduate degrees and fewer years of work experience were more likely to have a high intention to discriminate against people with HIV.ConclusionsIntention to discriminate against people with HIV was high among healthcare providers. Addressing HIV-related stigma constructs and understanding the differential effects of healthcare providers' sociodemographic and occupational characteristics on their discriminatory intentions are imperative to developing effective intervention to reduce intention to discriminate against people with HIV among healthcare providers.